Viral evolution: Primordial cellular origins and late adaptation to parasitism - Nasir, Arshan (Landes Bioscience, 2012)
Explaining the origin of viruses remains an important challenge for evolutionary biology. Previous explanatory frameworks described viruses as founders of cellular life, as parasitic reductive products of ancient cellular organisms or as escapees of modern genomes. Each of these frameworks endow viruses with distinct molecular, cellular, dynamic and emergent properties that carry broad and important implications for many disciplines, including biology, ecology and epidemiology. In a recent genome-wide structural phylogenomic analysis, we have shown that large-to-medium-sized viruses coevolved with cellular ancestors and have chosen the evolutionary reductive route. Here we interpret these results and provide a parsimonious hypothesis for the origin of viruses that is supported by molecular data and objective evolutionary bioinformatic approaches. Results suggest two important phases in the evolution of viruses: (1) origin from primordial cells and coexistence with cellular ancestors, and (2) prolonged pressure of genome reduction and relatively late adaptation to the parasitic lifestyle once virions and diversified cellular life took over the planet. Under this evolutionary model, new viral lineages can evolve from existing cellular parasites and enhance the diversity of the world’s virosphere.